The envelopes of amphibian oocytes: physiological modifications in Bufo arenarum - Sánchez Mercedes; Albertali Isabel E; Barisone Gustavo A; Cabada Marcelo O (BMC, 2003)
Abstract A characterization of the Amphibian Bufo arenarum oocyte envelope is presented. It was made in different functional conditions of the oocyte: 1) when it has been released into the coelomic cavity during ovulation (surrounded by the coelomic envelope, (CE), 2) after it has passed through the oviduct and is deposed (surrounded by the viteline envelope, (VE), and 3) after oocyte activation (surrounded by the fertilization envelope, (FE). The characterization was made by SDS-PAGE followed by staining for protein and glycoproteins. Labeled lectins were used to identify glycosidic residues both in separated components on nitrocellulose membranes or in intact oocytes and embryos. Proteolytic properties of the content of the cortical granules were also analyzed. After SDS-PAGE of CE and VE, a different protein pattern was observed. This is probably due to the activity of a protease present in the pars recta of the oviduct. Comparison of the SDS-PAGE pattern of VE and FE showed a different mobility for one of the glycoproteins, gp75. VE and FE proved to have different sugar residues in their oligosaccharide chains. Mannose residues are only present in gp120 of the three envelopes. N-acetyl-galactosamine residues are present in all of the components, except for gp69 in the FE. Galactose residues are present mainly in gp120 of FE. Lectin-binding assays indicate the presence of glucosamine, galactose and N-acetyl galactosamine residues and the absence (or non-availability) of N-acetyl-glucosamine or fucose residues on the envelopes surface. The cortical granule product (CGP) shows proteolytic activity on gp75 of the VE.